Retrospective cohort study of compliance with post-deployment screening in the Canadian Armed Forces. Issue 7 (19th July 2019) - Beliveau, Peter J H; Boulos, David; Johnson, Dylan
Abstract : Objective: Canadian Armed Forces (CAF) personnel who return from certain international deployments are required to complete post-deployment screening (PDS) 90 to 180 days post-deployment; the primary goal of PDS is early detection of mental health problems that aims for reduced delays to care provision. We investigated service members' compliance with the PDS completion requirement and the factors associated with this compliance; a secondary objective was to investigate completion timing. Design: The study used a retrospective cohort of CAF personnel (n=28 460) who had deployments over 01 January 2009 to 31 December 2014; inferences were based on a probabilistic sample (n=3004). Primary outcome: The primary outcome was PDS completion. We assessed the timing of PDS completion, comparing non-compliant (early, late or no completion) with compliant completions (90 to 180 days post-deployment) among deployments that required screening. Kaplan-Meier plots summarised time-to-completion and logistic regression assessed the covariate associations with compliant completion. Covariate-adjusted marginal compliance prevalence differences (MPD) were computed. Results: 67.3% (95% CI65.0 to 69.6) of deployments that required PDS had one completed; 43.3% (95%CI 40.6 to 46.0) were completed within the compliant period. Compliant completion was higher with lower ranks (MPD=10.6%, relative to officers), combat arms occupations (MPD=8.4%), Afghanistan deployments (MPD=19.2%), longer deployments (MPD=10.1%) and among those without a past mental health problem (MPD=9.7%). Conclusions: Our findings suggest that some selective processes may be occurring where those perceived to be at higher risk for post-deployment mental health problems are more compliant with PDS completion. However, PDS completion and compliant completion were lower than expected and this suggests a need to reinforce instruction on the guidelines and objectives of PDS among service members in the CAF.